Nitrogen-doped copper-containing antibacterial corrosion-resistant multi-component alloy and preparation method thereof
The nitrogen-doped copper-containing antibacterial corrosion-resistant multi-component alloy prepared through nitrogen doping technology solves the problem of traditional medical device materials being susceptible to microbial contamination during use, and achieves the coordinated improvement of antibacterial, corrosion resistance and mechanical properties. It is suitable for medical devices and other fields.
Patent Information
- Application Number
- CN202510067830.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-16
- Publication Date
- 2025-04-25
AI Technical Summary
Traditional medical device materials are susceptible to bacteria, fungi and other microorganisms during use, resulting in an increase in the risk of infection. It is difficult for copper-containing alloys to take into account both corrosion resistance and mechanical properties after improving their antibacterial properties.
Using nitrogen doping technology, a nitrogen-doped copper-containing antibacterial corrosion-resistant multi-component alloy is prepared. Its main components include Co, Cr, Ni, Si, Cu and N, and is produced by vacuum induction smelting, casting molding, hot forging, hot rolling, annealing and aging treatment processes.
It has achieved a coordinated improvement in the antibacterial properties, corrosion resistance and mechanical properties of the alloy, with excellent mechanical properties, excellent antibacterial properties and corrosion resistance, and is suitable for medical devices and other fields.
Smart Images

Figure CN119876732A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a multi-component alloy and a preparation method thereof, in particular to a nitrogen-doped copper-containing antibacterial and corrosion-resistant multi-component alloy and a preparation method thereof. Background Art
[0002] With the development of medical technology and the continuous improvement of performance requirements for medical devices, the infection problem of medical devices has become increasingly prominent. Although traditional medical device materials, such as stainless steel and titanium alloy, have good biocompatibility and mechanical properties and are widely used in surgical operations, orthopedic repairs, heart stents and other fields, they are susceptible to contamination by bacteria, fungi and other microorganisms during use, resulting in an increased risk of infection, which seriously affects the patient's recovery and life safety.
[0003] As a multifunctional metal element with multiple antibacterial and anti-inflammatory activities, copper has become a hot topic in the research of antibacterial materials. Studies have shown that copper ions can effectively inhibit the growth and reproduction of bacteria. In order to achieve bactericidal ability, copper-containing alloy materials need to be aged at a certain temperature to form a copper-rich precipitation phase (ε-Cu phase), and the precipitation of the ε-Cu phase is the key to antibacterial properties. When the alloy is exposed to a corrosive environment, the ε-Cu phase on the surface releases antibacterial copper ions into the surrounding environment, thereby inhibiting bacterial proliferation.
[0004] In order to achieve stable antibacterial function of copper-containing alloys, high copper content and appropriate aging treatment are required. However, the precipitation of a large amount of ε-Cu phase after aging not only causes pitting corrosion, but also may reduce the plasticity of the alloy, which seriously limits the potential application of copper-containing alloys in medical devices and other fields. Therefore, it is urgent to develop new alloy materials for medical devices that take into account antibacterial properties, corrosion resistance and mechanical properties. Summary of the invention
[0005] The object of the present invention is to provide a nitrogen-doped copper-containing antibacterial and corrosion-resistant multi-component alloy and a preparation method thereof, so as to solve the problems raised in the above-mentioned background technology.
[0006] To achieve the above-mentioned purpose, the present invention provides the following technical solution: a nitrogen-doped copper-containing antibacterial and corrosion-resistant multi-component alloy material, whose main components are composed according to the following atomic percentages: Co: 15.0-20.0%, Cr: 15.0-20.0%, Ni: 20.0-25.0%, Si: 4.0-6.0%, Cu: 1.5-3.5%, N: 0.2-2.5%, and the remaining components are Fe and unavoidable impurities.
[0007] As a preferred technical solution of the present invention, its components are composed according to the following atomic percentages: Co: 17.8-18.3%, Cr: 16.5-17.0%, Ni: 22.5-23.5%, Si: 4.8-5.2%, Cu: 2.8-3.2%, N: 0.5-2.0%, and the remaining components are Fe and unavoidable impurities.
[0008] Co element plays a role of solid solution strengthening, thereby improving the alloy's long-lasting strength and creep resistance. In addition, Co can also improve the alloy's hot working properties, plasticity and impact toughness. The preferred amount of Co used in the present invention is 17.8-18.3%.
[0009] The Cr element can not only protect the alloy from corrosion by forming a dense oxide film (passivation film), especially resist pitting and stress corrosion cracking, but also form a solid solution with Ni to further enhance corrosion resistance. The higher the Cr content, the more stable the passivation film and the better the corrosion resistance, but too high a Cr content will reduce the ductility and toughness of the alloy and reduce the machinability of the alloy, such as reducing welding performance. The preferred amount of Cr used in the present invention is 16.5-17.0%.
[0010] Fe is the main matrix material of the alloy, providing the alloy with basic structure and strength. At the same time, the presence of Fe also affects the phase change, corrosion resistance and processing performance of the alloy. Too high Fe content may cause the corrosion resistance of the alloy to decrease, especially the resistance to pitting and stress corrosion cracking. It will also reduce the strength and hardness of the alloy, making it difficult to meet specific application requirements. Too low Fe content may cause the stability of the alloy to decrease, or even cause embrittlement. The preferred Fe content of the present invention is 30.8-35.1%.
[0011] The Ni element has high chemical stability. It can not only improve the corrosion resistance of the alloy by forming a dense oxide film, especially resist pitting and stress corrosion cracking, but also form a solid solution with Cr to further enhance the corrosion resistance. At the same time, the Ni element can also effectively inhibit intergranular corrosion and improve the overall corrosion resistance of the alloy. In addition, the Ni element can also improve the strength and hardness of the alloy, stabilize the austenite phase, improve the processing performance of the alloy, and make it easier to process and shape. The preferred amount of Ni used in the present invention is 22.5-23.5%.
[0012] The addition of Si element can promote the formation of SiO2 passivation layer on the alloy surface and hinder the corrosion of metal elements in chlorine-containing environment. When the Si content is lower than 1.0%, the effect of Si element on the corrosion resistance of the alloy is small. When the Si content is higher than 1.0%, a Si-rich layer begins to form on the alloy surface, and the SiO2 passivation layer gradually thickens, improving the corrosion resistance of the alloy. As the Si content increases, the SiO2 passivation layer formed is thicker and denser, which effectively improves the corrosion resistance of the alloy. When the Si content is higher than 6.0%, a large number of large-sized G phases are formed in the alloy, which destroys the integrity of the passivation layer, reduces the corrosion resistance of the alloy, and at the same time reduces the ductility and toughness of the alloy, making it prone to brittle fracture, and may reduce the machinability of the alloy. Therefore, the preferred amount of Si used in the present invention is 4.8-5.2%.
[0013] The Cu element is a key factor in antibacterial properties, which determines the antibacterial effect of the alloy. Copper ions have a broad spectrum of antibacterial activity and can inhibit the growth and reproduction of bacteria. In order to achieve bactericidal ability, copper-containing alloy materials need to be aged at a certain temperature to form an ε-Cu phase, and the precipitation of the ε-Cu phase is the key to antibacterial properties. When the alloy is exposed to a corrosive environment, the ε-Cu phase on the surface releases antibacterial copper ions into the surrounding environment, thereby inhibiting bacterial proliferation. In order for copper-containing alloys to achieve stable antibacterial functions, high copper content and appropriate aging treatment are required. However, the precipitation of a large amount of ε-Cu phases after aging may cause pitting and intergranular corrosion, and also reduce the plasticity of the alloy. The preferred amount of Cu used in the present invention is 2.8-3.2%.
[0014] N is an important austenite stabilizing element, which is 30 times more effective than Ni and has an effect on pitting resistance that is 16 times that of Cr. In addition, it can also provide additional solid solution strengthening and increase the delay of sensitization. Adding N to the alloy significantly improves pitting resistance, reduces metastable pitting sensitivity, and enhances the stability of the passivation film material. In addition, N is also beneficial to improve the mechanical properties of stainless steel, medium entropy alloys and high entropy alloys. Therefore, adding a small amount of N has great potential to reduce the pitting sensitivity caused by ε-Cu phase precipitation. The preferred amount of N in the present invention is 0.5-2.0%
[0015] A method for preparing a Si-containing high entropy alloy material resistant to molten chloride corrosion comprises the following steps:
[0016] S1. Using vacuum induction melting process, when mixing raw materials, the main raw material components are mixed according to the following atomic percentage (%) composition: Co: 15.0-20.0%, Cr: 15.0-20.0%, Ni: 20.0-25.0%, Si: 4.0-6.0%, Cu: 1.5-3.5%, N: 0.2-2.5%, and the remaining components are Fe and unavoidable impurities. All the raw materials weighed after mixing are subjected to vacuum induction melting to obtain alloy melt;
[0017] S2. The alloy melt prepared in step S1 is cast into a mold, and the alloy ingot obtained by casting is subjected to hot forging, hot rolling, annealing and aging treatment processes in sequence to finally obtain nitrogen-doped copper-containing antibacterial and corrosion-resistant multi-component alloy material bars or plates.
[0018] Preferably, in step S1, the raw material components are prepared according to the following atomic percentage composition: Co: 17.8-18.3%, Cr: 16.5-17.0%, Ni: 22.5-23.5%, Si: 4.8-5.2%, Cu: 2.8-3.2%, N: 0.5-2.0%, and the remaining components are Fe and unavoidable impurities.
[0019] Preferably, in step S1, the weighed raw materials are mixed after batching, heated to 1500°C to 1600°C at a heating rate of not less than 10°C / min, and melted at the temperature for at least 10 minutes, and a vacuum induction melting process is used to obtain an alloy melt.
[0020] Preferably, in the step S2, the alloy melt prepared in the step S1 is cast and the alloy ingot obtained by casting is sequentially subjected to hot forging, hot rolling, annealing and aging treatment processes;
[0021] The hot forging temperature is controlled at 1200℃~1260℃, and the hot rolling temperature is controlled at 1120℃~1160℃. In order to avoid deformation and cracking during hot forging and hot rolling, the steel will be returned to the furnace for multiple times before forging / rolling during the hot deformation process.
[0022] Then, the alloy is annealed at 1000°C for 30 minutes, cooled to room temperature, and finally aged at 450°C for 6 hours to obtain nitrogen-doped copper-containing antibacterial and corrosion-resistant multi-component alloy material bars or plates.
[0023] Preferably, the alloy element Cu is dispersed and precipitated from the material matrix in the form of ε-Cu phase and is evenly distributed, and the room temperature tensile fracture strength of the material is not less than 850 MPa, and the elongation is not less than 20%.
[0024] Preferably, the antibacterial rate against Escherichia coli is greater than or equal to 95%.
[0025] Preferably, the pitting potential in 25°C, 3.5% NaCl solution is greater than or equal to 0.209V.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] 1. The present invention adopts nitrogen doping technology to improve the antibacterial properties of the alloy while effectively inhibiting the occurrence of pitting corrosion and improving the corrosion resistance of the alloy.
[0028] 2. It is difficult for traditional copper-containing alloy materials to take into account antibacterial properties, corrosion resistance and mechanical properties at the same time. Often, corrosion resistance or mechanical properties are sacrificed while antibacterial properties are improved. The present invention achieves a synergistic improvement in antibacterial properties, corrosion resistance and mechanical properties through nitrogen doping technology, providing a new solution for the development of antibacterial medical device materials.
[0029] 3. The nitrogen-doped copper-containing antibacterial and corrosion-resistant multi-component alloy material of the present invention has excellent mechanical properties after hot forging, hot rolling, annealing and aging treatment. Its room temperature tensile fracture strength is greater than or equal to 850 MPa, and its fracture elongation is greater than or equal to 20%, which can greatly improve the safety of the alloy during use;
[0030] 4. The nitrogen-doped copper-containing antibacterial and corrosion-resistant multi-component alloy material of the present invention has a simple production process, is easy to process, and is easy to promote and apply. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Attached Figure 1 The thermodynamic calculation phase diagram of the alloy of Example 1;
[0032] Attached Figure 2 This is a transmission image of the alloy microstructure of Example 1;
[0033] Attached Figure 3 This is a comparison chart of the antibacterial rates of Escherichia coli of the alloy of Example 1 and the non-nitrogen-doped multi-component alloy;
[0034] Attached Figure 4 This is a comparison diagram of the pitting potential of the alloy of Example 1, the non-nitrogen doped multi-component alloy, and 304 stainless steel in 3.5% NaCl solution. DETAILED DESCRIPTION
[0035] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0036] See also Figures 1 to 3The present invention provides a technical solution: a Si-containing high-entropy alloy material resistant to molten chloride corrosion, wherein the main components are composed of the following atomic percentages: Co: 10.0-30.0%, Cr: 10.0-30.0%, Ni: 10.0-30.0%, Al: 6.5-11.0%, Ti: 6.5-11.0%, Si: 1.0-30.0%, and the remaining components are Fe and unavoidable impurities.
[0037] Preferably, its components are composed according to the following atomic percentages: Co: 15.0-20.0%, Cr: 15.0-20.0%, Ni: 15.0-20.0%, Al: 8.0-10.5%, Ti: 8.0-10.5%, Si: 5.0-25.0%, and the remaining components are Fe and inevitable impurities.
[0038] The functions of each element in the formula are as follows:
[0039] The Co element plays a role in solid solution strengthening, thereby improving the alloy's long-lasting strength and creep resistance. At the same time, Co also reduces the solubility of Al and Ti elements in the matrix, thereby increasing the amount of γ' strengthening phase, and the solid solution temperature of the γ' phase also increases with the addition of Co. In addition, Co can also improve the alloy's hot working properties, plasticity and impact toughness. The preferred amount of Co in the present invention is 15.0-20.0%.
[0040] Cr element can increase the oxidation resistance and corrosion resistance of the alloy. When the Cr content reaches a critical value (above 15.0%), a continuous, dense and well-adhered Cr2O3 oxide film will form on the alloy surface, which can protect the metal surface from high-temperature oxidation and thermal corrosion caused by O, Cl, etc., and play a protective role against oxidation corrosion of the alloy. However, the increase in Cr content is bound to enhance the precipitation tendency of the Cr-rich body-centered α-Cr phase in the alloy. The preferred Cr content of the present invention is 15.0-20.0%.
[0041] The Fe element can not only improve the processing performance of the alloy but also reduce the material cost. The preferred amount of Fe in the present invention is 15.0-20.0%.
[0042] The Ni element has high chemical stability and is almost not oxidized below 500° C. It can dissolve various alloy elements without forming harmful phases. The preferred amount of Ni is 15.0-20.0%.
[0043] Al and Ti are the main elements that form the γ′ phase. Increasing the total amount of Al and Ti can significantly increase the solid solution temperature and volume fraction of the γ′ phase, and improve the mechanical properties of the alloy. As the Al and Ti content increases, the size of the γ′ phase gradually increases, and the γ′ phase morphology changes from spherical to cubic and then to irregular shape. Ti is also an MC-type carbide-forming element, forming a relatively stable TiC carbide, which delays or even prevents the carbide reaction at high temperatures, thereby stabilizing the Cr in the matrix and indirectly playing a role in resisting thermal corrosion. High Al is beneficial to improving the high-temperature oxidation resistance of the alloy. The preferred Al and Ti element dosages of the present invention are 8.0-10.5%, respectively.
[0044] The addition of Si element can promote the formation of SiO2 passivation layer on the alloy surface, hindering the dissolution of metal elements in molten chloride salt. When the amount of Si is higher than 1.0%, a Si-rich layer begins to form on the alloy surface, improving the corrosion resistance of the alloy; when the amount of Si is higher than 28.0%, a large-sized brittle Si-rich precipitate phase begins to form in the alloy, affecting the structural stability of the alloy. The preferred amount of Si in the present invention is 5.0-25.0%.
[0045] A method for preparing a Si-containing high entropy alloy material resistant to molten chloride corrosion comprises the following steps:
[0046] S1. Using vacuum induction melting process, when mixing raw materials, the main raw material components are mixed according to the following atomic percentage (%) composition: Co: 15.0-20.0%, Cr: 15.0-20.0%, Ni: 20.0-25.0%, Si: 4.0-6.0%, Cu: 1.5-3.5%, N: 0.2-2.5%, and the remaining components are Fe and unavoidable impurities. All the raw materials weighed after mixing are subjected to vacuum induction melting to obtain alloy melt;
[0047] S2. The alloy melt prepared in step a is cast into a mold, and the alloy ingot obtained by casting is subjected to hot forging, hot rolling, annealing and aging treatment processes in sequence to finally obtain nitrogen-doped copper-containing antibacterial and corrosion-resistant multi-component alloy material bars or plates.
[0048] In the step S1, the raw material components are prepared according to the following atomic percentage composition: Co: 17.8-18.3%, Cr: 16.5-17.0%, Ni: 22.5-23.5%, Si: 4.8-5.2%, Cu: 2.8-3.2%, N: 0.5-2.0%, and the remaining components are Fe and unavoidable impurities.
[0049] In the step S1, the weighed raw materials are mixed and heated at a heating rate of not less than 10°C / min to 1500°C-1600°C, and melted for at least 10 minutes by vacuum induction melting process to obtain an alloy melt.
[0050] In the step S2, the alloy melt prepared in the step S1 is cast into a mold, and the alloy ingot obtained by casting is subjected to hot forging, hot rolling, annealing and aging treatment processes in sequence;
[0051] The hot forging temperature is controlled at 1200℃~1260℃, and the hot rolling temperature is controlled at 1120℃~1160℃. In order to avoid deformation and cracking during hot forging and hot rolling, the steel will be returned to the furnace for multiple times before forging / rolling during the hot deformation process.
[0052] Then, the alloy is annealed at 1000°C for 30 minutes, cooled to room temperature, and finally aged at 450°C for 6 hours to obtain nitrogen-doped copper-containing antibacterial and corrosion-resistant multi-component alloy material bars or plates.
[0053] The nitrogen-doped copper-containing antibacterial and corrosion-resistant multi-component alloy of the present invention has the alloy element Cu dispersed and precipitated from the material matrix in the form of ε-Cu phase and evenly distributed. The room temperature tensile fracture strength of the material is not less than 850MPa and the elongation is not less than 20%.
[0054] The nitrogen-doped copper-containing antibacterial and corrosion-resistant multi-component alloy of the present invention has an antibacterial rate against Escherichia coli greater than or equal to 95%.
[0055] The pitting potential of the nitrogen-doped copper-containing antibacterial and corrosion-resistant multi-component alloy in a 3.5% NaCl solution at 25° C. is greater than or equal to 0.209V.
[0056] The above scheme is further described below in conjunction with specific implementation examples. The preferred embodiments of the present invention are described in detail as follows:
[0057] Embodiment 1:
[0058] In this embodiment, a nitrogen-doped copper-containing antibacterial and corrosion-resistant multi-component alloy material and a preparation method thereof include the following steps:
[0059] a. Using vacuum induction melting process, when mixing raw materials, the raw material components used are mixed according to the following atomic percentage (%) composition:
[0060]
[0061] The weighed raw materials are mixed, heated to 1500°C to 1600°C at a heating rate of not less than 10°C / min, and kept warm for at least 10 minutes, and a vacuum induction melting process is used to obtain an alloy melt;
[0062] b. Cast the alloy melt prepared in step a, and subject the alloy ingot obtained by casting to hot forging, hot rolling, annealing and aging treatment processes in sequence; wherein, the hot forging temperature is controlled to be 1200℃~1260℃, and the hot rolling temperature is 1120℃~1160℃. In order to avoid deformation and cracking during hot forging and hot rolling, the alloy will be returned to the furnace for many times and then forged / rolled during the hot deformation process. Afterwards, the alloy is annealed at 1000℃ for 30min and then cooled to room temperature, and finally aged at 450℃ for 6h to obtain nitrogen-doped copper-containing antibacterial and corrosion-resistant multi-component alloy material bars or plates.
[0063] After experimental testing, the alloy performance test results in this embodiment are as follows:
[0064] Microstructure: Figure 1 and Figure 2 It can be seen that after aging treatment at 450℃, the ε-Cu phase is dispersed and precipitated in the matrix and evenly distributed. The dispersed precipitation of the nanoscale ε-Cu phase can hinder the movement of dislocations, thereby improving the strength of the material. In terms of toughness, the dispersed distribution of the nanoscale ε-Cu phase can effectively hinder the propagation of cracks and provide additional plastic deformation mechanisms, thereby improving the toughness of the material. In addition, the presence of the nanoscale ε-Cu phase can effectively hinder the penetration of corrosive media, thereby improving the corrosion resistance of the material.
[0065] Mechanical properties: The room temperature tensile fracture strength of the alloy of Example 1 is 850 MPa, and the elongation is 28%, which has both high strength and good plasticity. This is due to the second phase strengthening of the uniformly distributed ε-Cu phase in the alloy and the solid solution strengthening effect brought about by nitrogen doping.
[0066] Antibacterial properties: Figure 3 It can be seen that the antibacterial rate of the alloy in Example 1 against Escherichia coli is 95%, showing excellent antibacterial effect, and is better than the non-nitrogen doped multi-component alloy (the composition of the non-nitrogen doped multi-component alloy does not contain N, and the other components are consistent with the alloy in Example 1). The improvement of the antibacterial properties of the alloy by nitrogen doping is mainly attributed to the following two aspects: First, the addition of the N element can increase the activity of Cu atoms in the alloy and promote the precipitation of the ε-Cu phase. The ε-Cu phase itself has good antibacterial properties, and its uniform distribution in the alloy can effectively inhibit the growth of bacteria. Secondly, nitrogen doping can promote the formation of a dense oxide film on the surface of the alloy, effectively preventing the attachment and reproduction of bacteria, and further enhancing the antibacterial effect of the alloy.
[0067] The antibacterial performance test steps are as follows:
[0068] The antibacterial test was conducted by coating method. Medical grade 304 stainless steel was used as the comparison steel, and the alloy of Example 1 and the non-nitrogen doped multi-component alloy were used as the experimental steel to study their antibacterial effects. The test sample size was 15×15×1.2 mm 3 The sample surface was ground to 2000# with silicon carbide metallographic sandpaper and then polished to a bright finish with diamond polishing agent. Escherichia coli was cultured in a standard medium consisting of 5.0 g / L meat extract, 5.0 g / L sodium chloride and 10.0 g / L peptide ester, and the pH was adjusted to 7.0-7.2. The medium and sample were automatically steam boiled at 120°C for 15 min. The concentration was 10 5 cfu / mL (colony forming unit) volume 0.4mL bacterial solution was dropped onto the surface of the test sample and then incubated in an LRH-70 incubator at 25°C for 24h. The bacterial solution on the sample was then washed with saline and diluted to 10 4 cfu / mL. Add 0.1 mL of the diluted bacterial solution to the nutrient agar plate and incubate at 37°C for 24 h. Count the number of colonies from the surviving bacteria and calculate the antibacterial rate according to the following formula:
[0069] Antibacterial rate (%) = (AB) / A × 100% (1)
[0070] Wherein, A is the colony count of the comparison stainless steel (medical grade 304 stainless steel), and B is the colony count of the experimental stainless steel. Three groups of parallel samples were prepared at the same time for antibacterial testing.
[0071] Corrosion resistance: Figure 4 It can be seen that the pitting potential of the alloy of Example 1 is 0.209V, which is significantly higher than that of the non-nitrogen doped multi-component alloy and 304 stainless steel, indicating that the alloy of Example 1 has better pitting resistance. The nitrogen doping process significantly improves the corrosion resistance of the multi-component alloy. Nitrogen doping can form a dense oxide film, which effectively prevents the penetration of corrosive media, thereby improving the corrosion resistance of the material. Nitrogen can reduce the potential gradient in the alloy passivation film, inhibit the entry of chloride ions, and once the passivation film is locally damaged, nitrogen ion segregation can induce the entering ions to desorb and repair the damage. In addition, the nitrogen element exists in the form of carbonitride in the form of Me2(C,N), which can reduce the formation of high chromium content carbides and reduce pitting sensitivity.
[0072] The corrosion performance test steps are as follows:
[0073] Polarization tests were performed on the alloy of Example 1, non-nitrogen-doped multi-component alloy, and 304 stainless steel using a CHI900D electrochemical workstation. Before testing, the sample surface was ground to 2000# metallographic sandpaper, mechanically polished to a bright surface, and then cleaned with alcohol. 2The samples were tested in 3.5wt.% NaCl solution at 25°C. A standard three-electrode system was used, with 1cm 2 The sample was used as the working electrode, the platinum sheet was used as the counter electrode, and the saturated calomel electrode was used as the reference electrode. During the polarization curve test, a scan rate of 1 mV / s was used, and the scan range was from -1.0 V to 1.0 V.
[0074] In summary, the nitrogen-doped copper-containing antibacterial and corrosion-resistant multi-component alloy material of this embodiment has both high strength and good plasticity, and exhibits excellent antibacterial and corrosion resistance. The dispersed precipitation of nanoscale ε-Cu phase in the material effectively improves the strength and toughness of the alloy, hinders the penetration of corrosive media, and improves corrosion resistance. The solid solution strengthening brought by nitrogen doping further improves the strength of the alloy, and promotes the formation of a dense oxide film on the surface of the alloy, enhancing the antibacterial and corrosion resistance. The excellent performance of this material gives it broad application prospects in fields such as medical devices.
[0075] Embodiment 2:
[0076] This embodiment is basically the same as the first embodiment, except that:
[0077] In this embodiment, a nitrogen-doped copper-containing antibacterial and corrosion-resistant multi-component alloy material and a preparation method thereof include the following steps:
[0078] a. Using vacuum induction melting process, when mixing raw materials, the raw material components used are mixed according to the following atomic percentage (%) composition:
[0079]
[0080] All the raw materials weighed after batching are subjected to vacuum induction melting to obtain an alloy melt;
[0081] b. This step is the same as in Example 1.
[0082] After experimental testing, the alloy performance test results in this embodiment are as follows:
[0083] Microstructure: After aging treatment at 450℃, the ε-Cu phase is dispersed and precipitated in the matrix and evenly distributed.
[0084] Mechanical properties: The room temperature tensile strength is 870MPa and the elongation is 25%. The higher nitrogen content brings a stronger solid solution strengthening effect, further improving the strength of the alloy.
[0085] Antibacterial properties: The antibacterial rate against E. coli is 97%. The increase in N content further enhances the antibacterial properties of the alloy.
[0086] Corrosion resistance: The pitting potential of the alloy of Example 2 is 0.223V, which is significantly higher than that of the non-nitrogen doped multi-component alloy and 304 stainless steel, indicating that the alloy of Example 2 has good pitting resistance. A higher nitrogen content further improves the corrosion resistance of the alloy.
[0087] The nitrogen-doped copper-containing antibacterial and corrosion-resistant multi-component alloy material in Example 2 further improves the strength, antibacterial and corrosion resistance of the material by increasing the nitrogen content on the basis of Example 1. This improvement is mainly due to the solid solution strengthening effect of nitrogen, the precipitation of ε-Cu phase and the formation of a dense oxide film. The material has both high strength and good plasticity, while showing excellent antibacterial and corrosion resistance, which gives it broad application prospects in medical devices and other fields.
[0088] Embodiment three:
[0089] This embodiment is basically the same as the first embodiment, except that:
[0090] In this embodiment, a nitrogen-doped copper-containing antibacterial and corrosion-resistant multi-component alloy material and a preparation method thereof include the following steps:
[0091] a. Using vacuum induction melting process, when mixing raw materials, the raw material components used are mixed according to the following atomic percentage (%) composition:
[0092]
[0093] All the raw materials weighed after batching are subjected to vacuum induction melting to obtain an alloy melt;
[0094] b. This step is the same as in Example 1.
[0095] After experimental testing, the alloy performance test results in this embodiment are as follows:
[0096] Microstructure: After aging treatment at 450℃, the ε-Cu phase is dispersed and precipitated in the matrix and evenly distributed.
[0097] Mechanical properties: The room temperature tensile strength is 885MPa and the elongation is 23%. The higher nitrogen content brings a stronger solid solution strengthening effect, further improving the strength of the alloy.
[0098] Antibacterial properties: The antibacterial rate against E. coli is 99%. The increase in N content further enhances the antibacterial properties of the alloy.
[0099] Corrosion resistance: The pitting potential of the alloy of Example 3 is 0.231 V, which is significantly higher than that of the non-nitrogen doped multi-component alloy and 304 stainless steel, indicating that the alloy of Example 3 has good pitting resistance. A higher nitrogen content further improves the corrosion resistance of the alloy.
[0100] The nitrogen-doped copper-containing antibacterial and corrosion-resistant multi-component alloy material in Example 3 further improves the strength, antibacterial and corrosion resistance of the material by increasing the nitrogen content. This improvement is mainly due to the solid solution strengthening effect of nitrogen, the precipitation of ε-Cu phase and the formation of a dense oxide film. The material has both high strength and good plasticity, while showing excellent antibacterial and corrosion resistance, giving it broad application prospects in medical devices and other fields.
[0101] Embodiment 4:
[0102] This embodiment is basically the same as the first embodiment, except that:
[0103] In this embodiment, a nitrogen-doped copper-containing antibacterial and corrosion-resistant multi-component alloy material and a preparation method thereof include the following steps:
[0104] a. Using vacuum induction melting process, when mixing raw materials, the raw material components used are mixed according to the following atomic percentage (%) composition:
[0105]
[0106] All the raw materials weighed after batching are subjected to vacuum induction melting to obtain an alloy melt;
[0107] b. This step is the same as in Example 1.
[0108] After experimental testing, the alloy performance test results in this embodiment are as follows:
[0109] Microstructure: After aging treatment at 450℃, the ε-Cu phase is dispersed and precipitated in the matrix and evenly distributed.
[0110] Mechanical properties: The room temperature tensile strength is 935MPa and the elongation is 20%. The higher nitrogen content brings a stronger solid solution strengthening effect, further improving the strength of the alloy.
[0111] Antibacterial properties: The antibacterial rate against E. coli is 99.5%. The increase in N content further enhances the antibacterial properties of the alloy.
[0112] Corrosion resistance: The pitting potential of the alloy of Example 4 is 0.243V, which is significantly higher than that of the non-nitrogen doped multi-component alloy and 304 stainless steel, indicating that the alloy of Example 4 has good pitting resistance. A higher nitrogen content further improves the corrosion resistance of the alloy.
[0113] The nitrogen-doped copper-containing antibacterial and corrosion-resistant multi-component alloy material in Example 4 further improves the strength, antibacterial and corrosion resistance of the material by increasing the nitrogen content. This improvement is mainly due to the solid solution strengthening effect of nitrogen, the precipitation of ε-Cu phase and the formation of a dense oxide film. The material has both high strength and good plasticity, while showing excellent antibacterial and corrosion resistance, giving it broad application prospects in medical devices and other fields.
[0114] In summary, the present invention provides a nitrogen-doped copper-containing antibacterial and corrosion-resistant multi-component alloy and a preparation method thereof, wherein the main components are composed according to the following atomic percentages (%): Co: 15.0-20.0%, Cr: 15.0-20.0%, Ni: 20.0-25.0%, Si: 4.0-6.0%, Cu: 1.5-3.5%, N: 0.2-2.5%, and the remaining components are Fe and inevitable impurities. The alloy is prepared by vacuum induction melting, casting, hot forging, hot rolling, annealing and aging treatment to finally obtain an antibacterial and corrosion-resistant alloy material bar or plate with excellent mechanical properties. The nitrogen-doped copper-containing antibacterial and corrosion-resistant multi-component alloy of the present invention has the advantages of good ductility, good antibacterial property, excellent corrosion resistance and hot working formability.
[0115] It is known from common technical knowledge that the present invention can be implemented by other embodiments that do not deviate from its spirit or essential features. Therefore, the above disclosed embodiments are only illustrative in all respects and are not exclusive. All changes within the scope of the present invention or within the scope equivalent to the present invention are included in the present invention.
Claims
1. A nitrogen-doped copper-containing antibacterial and corrosion-resistant multi-component alloy material, characterized in that: Its main components are composed according to the following atomic percentages: Co: 15.0-20.0%, Cr: 15.0-20.0%, Ni: 20.0-25.0%, Si: 4.0-6.0%, Cu: 1.5-3.5%, N: 0.2-2.5%, and the remaining components are Fe and inevitable impurities.
2. The nitrogen-doped copper-containing antibacterial and corrosion-resistant multi-component alloy material according to claim 1, characterized in that: Its components are composed according to the following atomic percentages: Co: 17.8-18.3%, Cr: 16.5-17.0%, Ni: 22.5-23.5%, Si: 4.8-5.2%, Cu: 2.8-3.2%, N: 0.5-2.0%, and the remaining components are Fe and inevitable impurities.
3. A method for preparing a nitrogen-doped copper-containing antibacterial and corrosion-resistant multi-component alloy material according to claims 1-2, characterized in that: The following steps are involved: S1. Using vacuum induction melting process, when mixing raw materials, the main raw material components are mixed according to the following atomic percentage (%) composition: Co: 15.0-20.0%, Cr: 15.0-20.0%, Ni: 20.0-25.0%, Si: 4.0-6.0%, Cu: 1.5-3.5%, N: 0.2-2.5%, and the remaining components are Fe and unavoidable impurities. All the raw materials weighed after mixing are subjected to vacuum induction melting to obtain alloy melt; S2. The alloy melt prepared in step a is cast into a mold, and the alloy ingot obtained by casting is subjected to hot forging, hot rolling, annealing and aging treatment processes in sequence to finally obtain nitrogen-doped copper-containing antibacterial and corrosion-resistant multi-component alloy material bars or plates.
4. A preparation method according to claim 3, characterized in that: In the step S1, the raw material components are prepared according to the following atomic percentage composition: Co: 17.8-18.3%, Cr: 16.5-17.0%, Ni: 22.5-23.5%, Si: 4.8-5.2%, Cu: 2.8-3.2%, N: 0.5-2.0%, and the remaining components are Fe and unavoidable impurities.
5. A preparation method according to claim 3, characterized in that: In the step S1, the weighed raw materials are mixed and heated at a heating rate of not less than 10°C / min to 1500°C-1600°C, and melted for at least 10 minutes by vacuum induction melting process to obtain an alloy melt.
6. A preparation method according to claim 3, characterized in that: In the step S2, the alloy melt prepared in the step S1 is cast into a mold, and the alloy ingot obtained by casting is subjected to hot forging, hot rolling, annealing and aging treatment processes in sequence; The hot forging temperature is controlled at 1200℃~1260℃, and the hot rolling temperature is controlled at 1120℃~1160℃. In order to avoid deformation and cracking during hot forging and hot rolling, the steel will be returned to the furnace for multiple times before forging / rolling during the hot deformation process. Then, the alloy is annealed at 1000°C for 30 minutes, cooled to room temperature, and finally aged at 450°C for 6 hours to obtain nitrogen-doped copper-containing antibacterial and corrosion-resistant multi-component alloy material bars or plates.
7. The nitrogen-doped copper-containing antibacterial and corrosion-resistant multi-component alloy material according to claim 1, characterized in that: The alloy element Cu is dispersed and precipitated from the material matrix in the form of ε-Cu phase and is evenly distributed. The room temperature tensile fracture strength of the material is not less than 850 MPa and the elongation is not less than 20%.
8. The nitrogen-doped copper-containing antibacterial and corrosion-resistant multi-component alloy material according to claim 1, characterized in that: The antibacterial rate against Escherichia coli is greater than or equal to 95%.
9. The nitrogen-doped copper-containing antibacterial and corrosion-resistant multi-component alloy material according to claim 1, characterized in that: The pitting potential in 3.5% NaCl solution at 25°C is greater than or equal to 0.209V.